Clinical Practice Guidelines for intestinal occlusion. - Rudis Miguel Monzón Rodríguez; Carlos Jaime Geroy Gómez; Francisco García Valdéz; Jorge Luis Ulloa Capestany; Maribel Misas Menéndez (Medisur)
Clinical Practice Guidelines for intestinal occlusion. This document includes the main aspects related with classification, physiopathology, clinical diagnosis, complementary examinations and therapy aimed at the post-operatory treatment. It includes assessment guidelines focused on the most important aspects to be accomplished.